Post-Disaster Temporary Shelter Area Selection and Planning by Using Delphi Method: Izmir/Seferihisar Case - Hande Dayanır; Ali Kemal Çınar; Yenal Akgün; Özşen Çorumluoğlu (Doğal Afetler ve Çevre Dergisi)
Site selection of the post-disaster temporary shelter areas and their site plan designs constitute one of the most important issues of disaster and risk management studies. In Turkey, the Disaster and Emergency Management Presidency (AFAD) coordinates this research. Although the "Directive on the Establishment, Management and Operation of Temporary Shelter Centers" released by AFAD in 2015 mostly defines the national criteria, it is not as detailed as the regulations revealed in the international literature. Moreover, the criteria announced in this directive are not ranked according to their importance. As another important gap, convenience of the post-disaster temporary shelter areas suggested by AFAD for the province of Izmir has not been yet evaluated according to the national and international legislations. In order to meet these gaps, the first aim of this study is to compile, group, define and rank the criteria for the site selection and planning of post-disaster temporary shelter areas using Delphi method. The second aim of the study is to analyze the convenience of the post-disaster temporary shelter areas, which were suggested for Izmir by AFAD, using the site selection/planning criteria put forward by the Delphi method. According to the criteria list formed as a result of the three-stage Delphi panels, it has been determined that a limited number of areas in Izmir can meet the requirements. It has been explained why Seferihisar2, one of these areas, is the most suitable area, and a sample container-city site plan has been made on the area based on the design/implementation criteria obtained with the Delphi method.